Bead Maze Media Semiotics Objects: A Study of Mathematics Teaching for Autism Students in Elementary School - Olga Putriana Wati; Dyah Worowirastri Ekowati; Toto Nusantara; Makbul Muksar; Dwi Agus Sudjimat (Universitas Pendidikan Ganesha, 2023)
Mathematics learning for autistic students needs to be done concretely and interestingly. If this is implemented, it is hoped that autistic students will be able to understand and even use mathematics in everyday life. This study aimed to analyze semiotic objects in the bead maze media for learning mathematics for autistic students in elementary schools. The research was conducted in a descriptive qualitative manner. Methods of data collection through observation, documentation, and interviews with elementary school mathematics teachers and assistants for autistic students. Observations were made by observing the bead maze adaptive media. Objects that can be observed are the beads in it, such as different shapes and colors. Interviews were conducted with one third-grade autistic student, an elementary school math teacher, and an assistant teacher. Data obtained from observation, documentation, and interviews were then analyzed using triangulation. The triangulation methodology is carried out by comparing the information obtained from observation, documentation, and interviews. The study results found that six primary semiotic objects, namely language, problem situations, concepts, procedures, properties, and arguments, have been identified based on basic mathematical concepts (numbers, algebra, geometry, measurement) being studied in the third grade. Each semiotic object in bead maze media can potentially increase students' mathematical activities, which are contextual, interesting, and meaningful for autistic students in elementary schools.